Export horticulture – empowering female small-scale farmers in Kenya? - Velte, Maria; Dannenberg, Peter (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Export horticulture is one of Kenya’s most dynamic sectors, with the Mount Kenya Region playing a crucial role as a result of its professional large- and small-scale production and marketing structures. The sector is consequently referred to as a “success story of African regional development” (Dolan and Sutherland 2002: 1). A qualitative case study was carried out to understand the impacts on gender inequality of the integration of horticultural smallholdings into the fresh fruit and vegetable (FFV) supply chain to the European market. It will be outlined how export horticulture affects female small-scale farmers with reference to local distribution channels, the organisation of the farm as a group or an individual player, and the specific organisation of labour on the farm. The focus here is on the traditional division of labour, ownership and mobility patterns, as well as on knowledge and income. The study shows that the influence of the integration in the FFV chain on gender inequality is conditioned by both the type of relations to the buyers and the internal and institutional organisation of the smallholding. Surprisingly, in some areas of the primarily male-dominated rural society, an integration in the form of outgrower schemes that resembles Gereffi et al.’s model of a captive value chain, with women farmers exclusively responsible for export production, can enhance gender equality, as women gradually gain more decision-making power and greater independence.